Urban Memory and Visual Culture in Berlin : Framing the Asynchronous City, 1957-2012 - Ward, Simon, 1969- (Book collections on Project MUSE., 2016)
"This book examines the crucial role of visual culture (architecture, memorials, photography and film) in shaping Berlin's urban memory culture in both East and West in response to the changing political, social and economic organization of the built environment over the past five decades."